perimeter of right triangle is 12 cm its hypotenuse is 5cm . find length of other two sides.
Answers
Answered by
0
14 and 143 according to pytha goras theorem
Answered by
1
One way is two directly think of a right triangle with hypotenuse 5, which in this case is 3,4,5 triangle.
However, when the length of the hypotenuse is greater, this might not work. So , here is the universal method!!
Let the length of the other two legs be x and y.
Now given that
![x + y + 5 = 12 \\ x + y = 7 x + y + 5 = 12 \\ x + y = 7](https://tex.z-dn.net/?f=x+%2B+y+%2B+5+%3D+12+%5C%5C+x+%2B+y+%3D+7)
And by Pythagoras Theorem,
![{x}^{2} + {y}^{2} = {5}^{2} \\ {x}^{2} + {y}^{2} = 25 {x}^{2} + {y}^{2} = {5}^{2} \\ {x}^{2} + {y}^{2} = 25](https://tex.z-dn.net/?f=++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++%3D++%7B5%7D%5E%7B2%7D++%5C%5C++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++%3D+25)
Now consider this,
![{(x + y)}^{2} = {x}^{2} + {y}^{2} + 2xy \\ {x}^{2} + {y}^{2} = {(x + y)}^{2} - 2xy {(x + y)}^{2} = {x}^{2} + {y}^{2} + 2xy \\ {x}^{2} + {y}^{2} = {(x + y)}^{2} - 2xy](https://tex.z-dn.net/?f=+%7B%28x+%2B+y%29%7D%5E%7B2%7D++%3D++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D+%2B+2xy++%5C%5C++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++%3D++%7B%28x+%2B+y%29%7D%5E%7B2%7D++-+2xy)
Substitute this to get
![{(x + y)}^{2} - 2xy = 25 \\ {7}^{2} - 2xy = 25 \\ 49 - 25 = 2xy \\ 24 = 2xy \\ xy = 12 {(x + y)}^{2} - 2xy = 25 \\ {7}^{2} - 2xy = 25 \\ 49 - 25 = 2xy \\ 24 = 2xy \\ xy = 12](https://tex.z-dn.net/?f=+%7B%28x+%2B+y%29%7D%5E%7B2%7D++-+2xy+%3D+25+%5C%5C++%7B7%7D%5E%7B2%7D+-+2xy+%3D+25+%5C%5C+49+-+25+%3D+2xy+%5C%5C+24+%3D+2xy+%5C%5C+xy+%3D+12+)
Now think of numbers that on adding give 7 and on multiplying give 12.
Clearly such numbers are 3 and 4 and so you have your answer.
Or, once again,
![x + y = 7 \\ y = 7 - x x + y = 7 \\ y = 7 - x](https://tex.z-dn.net/?f=x+%2B+y+%3D+7+%5C%5C+y+%3D+7+-+x)
Substitute this,
![x(7 - x) = 12 \\ 7x - {x}^{2} = 12 \\ {x - 7x }^{2} + 12 = 0 x(7 - x) = 12 \\ 7x - {x}^{2} = 12 \\ {x - 7x }^{2} + 12 = 0](https://tex.z-dn.net/?f=x%287+-+x%29+%3D+12+%5C%5C+7x+-++%7Bx%7D%5E%7B2%7D++%3D+12+%5C%5C++%7Bx+-+7x+%7D%5E%7B2%7D++%2B+12+%3D+0)
Solving this, u get
![(x - 3)(x - 4) = 0 \\ x = 3 \\ x = 4 (x - 3)(x - 4) = 0 \\ x = 3 \\ x = 4](https://tex.z-dn.net/?f=%28x+-+3%29%28x+-+4%29+%3D+0+%5C%5C+x+%3D+3+%5C%5C+x+%3D+4)
Substitute any of these into the xy equation and you have your answer.
However, when the length of the hypotenuse is greater, this might not work. So , here is the universal method!!
Let the length of the other two legs be x and y.
Now given that
And by Pythagoras Theorem,
Now consider this,
Substitute this to get
Now think of numbers that on adding give 7 and on multiplying give 12.
Clearly such numbers are 3 and 4 and so you have your answer.
Or, once again,
Substitute this,
Solving this, u get
Substitute any of these into the xy equation and you have your answer.
Similar questions
Math,
9 months ago
Math,
9 months ago
Social Sciences,
1 year ago
Sociology,
1 year ago
English,
1 year ago